1991
DOI: 10.1021/np50073a004
|View full text |Cite
|
Sign up to set email alerts
|

New Polyhydroxy Sterols, Dysidamides, and a Dideoxyhexose from the Sponge Dysidea herbacea

Abstract: Six novel marine natural products, dysidamides B [3] and C [5], three highly oxygenated sterols 9, 11, and 13, and a 1,4-dideoxyhexose 15 were isolated from the Red Sea sponge Dysidea herbácea, along with the previously known 24-methylene-5ot-cholest-7--3ß,5,6ß-« 1 [7], furodysinin lactone, and -D-xy lopy ranose. Structures of all new compounds were determined from spectroscopic data, especially extensive ID and 2D nmr experiments.Many interesting metabolites have been isolated from Dysidea species (1-7). Rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 11 publications
2
34
0
Order By: Relevance
“…The observation of cross-peaks in the HMBC between the signal at 5.20 ppm with the 13 C signals corresponding to C5, C9 and C14 and the cross peaks for the signal at 3.50 ppm with the 13 C signals corresponding to C5, C7, C8 and C10 indicate the epoxide is in the 5,6 position. The down®eld chemical shift of the 3b-hydroxy methine at 3.90 ppm is consistent with the a stereochemistry for the 5, 6-epoxy group (Aiello, Fattorusso, Magno, Mayol & Menna, 1990;Isaacs, Berman & Kashman, 1991;Venkateswarlu, Reddy & Rao, 1996). 5a, 6a-Epoxy sterols similar to compound 2 are unknown.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…The observation of cross-peaks in the HMBC between the signal at 5.20 ppm with the 13 C signals corresponding to C5, C9 and C14 and the cross peaks for the signal at 3.50 ppm with the 13 C signals corresponding to C5, C7, C8 and C10 indicate the epoxide is in the 5,6 position. The down®eld chemical shift of the 3b-hydroxy methine at 3.90 ppm is consistent with the a stereochemistry for the 5, 6-epoxy group (Aiello, Fattorusso, Magno, Mayol & Menna, 1990;Isaacs, Berman & Kashman, 1991;Venkateswarlu, Reddy & Rao, 1996). 5a, 6a-Epoxy sterols similar to compound 2 are unknown.…”
Section: Resultssupporting
confidence: 66%
“…5a, 6a-Epoxy sterols similar to compound 2 are unknown. A small number of 5a, 6a-epoxy sterols have been isolated from marine sponges and corals (Aiello et al, 1990;Isaacs, Berman & Kashman, 1991;Venkateswarlu, Reddy & Rao, 1996;Kobayashi & Kanda, 1991) and have been shown to have cytotoxic activities.…”
Section: Resultsmentioning
confidence: 99%
“…The high-frequency chemical shift of the 3˛-hydroxy methine at υ 3.90 is consistent with its deshielding by˛-stereochemistry of the 5,6-epoxy group. 5,6 Thě -orientation of H-6 was deduced from the its NOESY correlation with H-7ˇat υ 1.88, which in turn showed a NOESY correlation with H-8ˇat υ 1.34. These data showed that the protons mentioned above were on the sameˇface of the ring.…”
Section: Resultsmentioning
confidence: 99%
“…77 Three highly oxygenated sterols (230-232) were isolated from the Red Sea sponge Dysidea herbacea, along with the previously known compound 24-methylene-5α-cholest-7-ene-3β,5,6β-triol (233). 78 In 2001, as part of a search for novel inhibitors of human deficiency virus type 1 (HIV-1) reverse transcriptase (RT), the methanol ethyl acetate extract of a Red Sea sponge, Clathria sp., was shown to be active. Bioassay-guided fractionation of the extract yielded a sterol sulfate, clathsterol (234), which was responsible for the activity and was found to be active at a concentration of 10 mM.…”
Section: Sterols and Steroidal Glycosidesmentioning
confidence: 99%
“…97 Dysidamides B (288), dysidamide C (289), and a 1,4-dideoxyhexose (290) were isolated from the Red Sea sponge Dysidea herbacea, along with the previously known furodysinin lactone (291), and α-D-xylopyranose (292). 78 Two hexapreynylhydroquinone-derived disulfates, shaagrockol B (293) and C (294) were obtained from the Red Sea sponge Toxiclona toxius. 98 Four hexaprenoid hydroquinone sulfates, toxicols A-C (295-297) and toxiusol A (298) were isolated from the Red Sea sponge Toxiclona toxius.…”
Section: Other Metabolitesmentioning
confidence: 99%